2017
DOI: 10.1007/s00429-017-1470-7
|View full text |Cite
|
Sign up to set email alerts
|

Volume electron microscopy of the distribution of synapses in the neuropil of the juvenile rat somatosensory cortex

Abstract: Knowing the proportions of asymmetric (excitatory) and symmetric (inhibitory) synapses in the neuropil is critical for understanding the design of cortical circuits. We used focused ion beam milling and scanning electron microscopy (FIB/SEM) to obtain stacks of serial sections from the six layers of the juvenile rat (postnatal day 14) somatosensory cortex (hindlimb representation). We segmented in three-dimensions 6184 synaptic junctions and determined whether they were established on dendritic spines or dendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
63
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 63 publications
12
63
1
2
Order By: Relevance
“…It has also been consistently reported that the neuropil is characterized by a much higher number of excitatory contacts compared to inhibitory synapses in different brain regions and species (4,11,(27)(28)(29)(30). In the present study, the density of inhibitory synapses was particularly low in most CA1 layers (AS:SS ratio in all layers was around 95:5 except for in SLM, where the ratio was close to 90:10).…”
Section: Spatial Synaptic Distribution Proportion Of Synapses and Posupporting
confidence: 70%
See 2 more Smart Citations
“…It has also been consistently reported that the neuropil is characterized by a much higher number of excitatory contacts compared to inhibitory synapses in different brain regions and species (4,11,(27)(28)(29)(30). In the present study, the density of inhibitory synapses was particularly low in most CA1 layers (AS:SS ratio in all layers was around 95:5 except for in SLM, where the ratio was close to 90:10).…”
Section: Spatial Synaptic Distribution Proportion Of Synapses and Posupporting
confidence: 70%
“…Regarding postsynaptic preferences, we observed a clear preference of excitatory axons and inhibitory axons for dendritic spines and dendritic shafts, respectively, which is also characteristic in other cortical regions and species, although variations in their percentages have been reported (4,12,27,28,(30)(31)(32). For example, axospinous AS are especially abundant in sSP (87.61%) when compared to other brain regions in both humans and other species such as layer II of the human transentorhinal cortex, where axospinous AS account for only 55% of the total synaptic population (12).…”
Section: Spatial Synaptic Distribution Proportion Of Synapses and Posupporting
confidence: 60%
See 1 more Smart Citation
“…It has been consistently reported that the neuropil is characterized by a much higher number of excitatory contacts compared to inhibitory synapses in different brain regions and species 34,35,36,37,38,39,24 . In the present study, we found that the AS:SS ratio was 96.25:3.75.…”
Section: Ratio Of As and Ssmentioning
confidence: 98%
“…However, it has been well established via electron microscopy that dendritic shafts also form synapses and not all dendritic spines represent postsynaptic targets 23,24,25 . Thus, electron microscopy with serial section reconstruction is the gold standard method for studying the normal synaptic organization and its possible alterations.…”
Section: Introductionmentioning
confidence: 99%